2013
DOI: 10.4161/pri.23286
|View full text |Cite
|
Sign up to set email alerts
|

The neurodegeneration in Alzheimer disease and the prion protein

Abstract: The concept of "prion-like" has been proposed to explain the pathogenic mechanism of the principal neurodegenerative disorders associated with protein misfolding, including Alzheimer disease (AD). Other evidence relates prion protein with AD: the cellular prion protein (PrP(C)) binds β amyloid oligomers, allegedly responsible for the neurodegeneration in AD, mediating their toxic effects. We and others have confirmed the high-affinity binding between β amyloid oligomers and PrP(C), but we were not able to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…In our hands, the high‐affinity binding of Aβ oligomers to cellular prion protein has been confirmed, but behavioral experiments to evaluate the functional consequence of this interaction did not support a substantial role of prion protein in the Aβ oligomer‐induced neuronal dysfunction . This, however, does not rule out that peptides analogous to the prion sequence could be used to neutralize Aβ oligomer activity in a therapeutic perspective …”
Section: Aβ Oligomersmentioning
confidence: 65%
See 1 more Smart Citation
“…In our hands, the high‐affinity binding of Aβ oligomers to cellular prion protein has been confirmed, but behavioral experiments to evaluate the functional consequence of this interaction did not support a substantial role of prion protein in the Aβ oligomer‐induced neuronal dysfunction . This, however, does not rule out that peptides analogous to the prion sequence could be used to neutralize Aβ oligomer activity in a therapeutic perspective …”
Section: Aβ Oligomersmentioning
confidence: 65%
“…82 This, however, does not rule out that peptides analogous to the prion sequence could be used to neutralize Ab oligomer activity in a therapeutic perspective. 83,84 Kim et al 85 identified 2 new receptors for aggregated Ab, namely, the mouse paired immunoglobulin-like receptor B and its human ortholog, leukocyte immunoglobulin-like receptor. This interaction activates a signaling cascade that affects the neuronal actin cytoskeleton, causing synaptic loss in a mouse model of AD.…”
Section: O L I G O M E R O P a T H I E Smentioning
confidence: 99%
“…[1][2][3][4][5] In these disorders, the abnormal forms of target proteins are essential for pathogenesis. [1][2][3][4][5] In these disorders, the abnormal forms of target proteins are essential for pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence together with genetic studies, identifying AD associated autosomal dominant mutations in the sequence of the amyloid precursor protein (APP) or presenilin 1 and 2 (PS1 and 2) involved in APP metabolism, has attributed to Ab deposits an essential role in AD pathogenesis. In the last decade the small soluble aggregates of Ab, named oligomers, rather than the fibrillar forms, have been considered responsible for the neuronal dysfunction (Benilova et al, 2012;Forloni et al, 2013). Although, synaptotoxic effect of Ab, oligomers is well established in cell culture and transgenic (Tg) animal models of AD, the extent and significance of this effect in humans is unclear.…”
Section: Introductionmentioning
confidence: 99%